KINERJA BADAN PENANGGULANGAN BENCANA DAN PEMADAM KEBAKARAN DAERAH KABUPATEN PELALAWAN (STUDI KASUS BENCANA KEBAKARAN HUTAN DAN LAHAN 2014) - Suci Ardianti Fera; Zaili Rusli. SD (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
As for intention of this research is to know Body performance of counterneasures Disaster and fire company of Area Sub-Province of Pelalawan ( Case Study Disaster Forest Fire and Farm) Year 2014 and to know factor - factor resistor of performance ( Good study of Case Disaster Forest Fire and Farm) Year 2014.This research is done/conducted by in Body of counterneasures Disaster and Fire Company Of Area Sub-Province of Pelalawan, taken by officer of body of counterneasures Disaster and Fire Company Of Area Sub-Province of Pelalawan made by informan by method of snowball sampling. In line with research which have been mentioned by above, hence needed data, for example primary data and data of sekunder. For the technique of data collecting done/conducted] with interview technique, bibliography study and observation. Method analyse data which is used in this research is descriptive analysis method qualitative.Result of research indicate that performance officer of Body of counterneasures Disaster and Fire Company Of Sub-Province of Pelalawan in winning case kebakaran of farm and forest in Sub-Province of Pelalawan done/conducted by is officer have been put accross.. In doing/conducting attainment of performance officer of Body of counterneasures Disaster and Fire Company Of Sub-Province of Pelalawan in handling forest fire and farm there are some factor influencing it for example : ( a). Inexistence standard measuring instrument of[is make-up of performance, ( b). inexistence record-keeping of result assessment of and performance ( c). Still there are less owning officer of ability of job/activity.Keyword : Performance, Body of counterneasures Disaster and Fire Company Of Sub-Province of Pelalawan